Theory of Cascade Mining of Open PIT Fields - Mirzhanovna , Samadova Guli; ugli, Tuychiboev Zahriddin Ilhom (Researchparks Publishing, 2023)
This article examines the difference in the technology of mining operations in conventional and cascade staged development of upland deposits, as well as The difference between the methods of opening from the traditional, without stage development, methods of formation of pillars and their development.